Psychosocial function in the first year after childhood stroke. (25th January 2017) - Greenham, Mardee; Anderson, Vicki; Hearps, Stephen; Ditchfield, Michael; Coleman, Lee; Mackay, Mark T; Monagle, Paul; Gordon, Anne L
Abstract : Aim: Childhood stroke disrupts brain development and emerging neural networks. Motor, cognitive, and language deficits are well recognized, yet little is known about psychosocial function after childhood stroke. This study aims to describe psychosocial function within the first year after childhood stroke, and to identify factors associated with outcome. Method: Thirty‐seven children were involved in a prospective, longitudinal study investigating recovery over the first year after childhood stroke. Children's social functioning was assessed at 6‐months and 12‐months poststroke and psychological function at 12‐months poststroke, using standardized measures. Results: Mean social function was poorer at both 6‐months and 12‐months poststroke, compared to prestroke. Psychological problems were more common than expected, with emotional difficulties and hyperactivity–inattention most significantly affected. Poorer social function was associated with older age at onset, acute neurological impairment, and prestroke social impairment. Social and psychological problems were associated with parent mental health. Interpretation: While not all children are affected, psychosocial impairment affects a significant minority after childhood stroke. Older age at onset, acute neurological impairment, prestroke social problems, and poorer parent mental health were associated with deficits. Identifying early predictors of poorer outcome will facilitate early intervention. Of particular importance is parent mental health, suggesting support for families may improve child outcome. What this paper adds: Children are at elevated risk of psychosocial impairment after childhood stroke. Psychosocial impairments may begin to emerge within the first 12 months of recovery. Children who have stroke onset at an earlier age appear to have better social outcomes. Parent mental health is associated with child psychosocial outcomes. This article is commented on by Westmacott on pages991–992 of this issue.